Perspectives on Energy Insecurity and Its Impacts on Urban Livelihoods: Adaptation and Resilience of Women in the Informal Sector - Reid, Memory; Simatele, Mulala Danny (Frontiers in Sustainable Cities, 2021)
Variability in temperature and precipitation due to climate change is predicted to significantly impact on Southern African countries’ resources. These variations have the potential to affect the energy sector due to a heavy reliance on hydropower for electricity in the region. Energy insecurity is largely felt in cities as they are large consumers of the resource. This negatively impacts on urban livelihoods reliant on electricity like those in the informal sector. A survey of electricity dependent home-based informal businesses was conducted to generate information on the vulnerability of urban livelihoods to energy insecurity in Zimbabwe. Households across all socio-economic backgrounds performed informal businesses to supplement/generate household income and were heavily depended on the irregular electricity supply. Poor households were disproportionately affected by the unstable electricity supply as they could not afford alternative energy sources to continue business operations during power cuts. This accentuated the low adaptive capacity and vulnerability of the urban poor to climate change induced stresses. This paper brings to light the importance of improving the resilience and adaptive capacity of urban livelihoods to climate change induced stresses like energy security whilst exploring climate-resilient energy options to sufficiently mitigate against the impacts of climate change on energy security.